Pertanggungjawaban atas Kehilangan atau Kerusakan Barang yang Dilakukan oleh Transportasi Berbasis Online Ditinjau Dari Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Solikin; Helmi; Salom (LPPM STIH Awang Long, 2020)
In Indonesia, there are 3 (three) types of transportation, namely land transportation, sea transportation, and air transportation.5 Of the three types of transportation, road transportation is the medium most often used by passengers when compared to other transportation. The characteristics of people's transportation can be divided into private transportation and public transportation. Paratransit public transportation is transportation that does not have a fixed route and schedule in operation along its route, while mass-transit public transportation is transportation that has a fixed route and schedule, as well as a clear stopping place. Motorcycles are included in the classification of types of private vehicles, but nowadays motorbikes also perform the function of public transportation, namely transporting people and/or goods and collecting agreed fees. This kind of transportation is known as ojek. Ojek Online is an online application-based transportation that plays a very important role in delivering goods within the city. The author wants to examine what if the goods sent through this online-based application are damaged or lost in terms of Law No. 22 of 2009 concerning Road Traffic and Transportation. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed.